ANALISIS HUBUNGAN KECEPATAN TERHADAP KECELAKAAN LALU-LINTAS DI KOTA BANJARMASIN - Huddan Rahmani; Akhmad Gazali; Jarkawi Jarkawi; Muhammad Isran Ramli (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2019)
Many factors cause traffic accidents where the driving speed is one of the main causes, and this is known from several studies conducted in universities in the city of Banjarmasin, which chronologically the accident events mostly stated that the vehicles involved in the accident were driven at high speed. The results of recording the speed on the road segment studied violations exceeding the speed limit that is at night before dawn, and this applies to almost all types of vehicles in both directions of the lane at that time the traffic volume decreases. The majority of respondents think that high speed